Antibacterial Naphthaquinones from Necterium sp. Inhabited in Tinospora cordifolia (Bangladesh Pharmaceutical Journal, 2022)
Numerous biologically active metabolites have previously been obtained from endophytes including endophytic fungi. This potentiality and prospect prompted us to find out new compounds having activity against pathogenic bacteria, from fungal endophyte, Necterium sp. isolated from the leaf of Tinospora cordifolia. We cultivated and developed the fungal strains on PDA medium and extracted on ethyl acetate after 28 days. Column chromatographic technique followed by preparative TLC was utilized to isolate secondary metabolites as pure crystalline solid. Two naphthoquinones namely anhydrofusarubin (1) and fusarubin methyl ether (2) were isolated from Necterium sp. The 1H and 13C NMR spectral data of the isolated compounds were analyzed and compared with previously published values to confirm the structure of the compounds. The compounds were assessed for antibacterial activity by resazurin based microdilution assay. Both of them showed sensitivity towards gram negative Pseudomonas aeruginosa but none was active against Staphylococcus aureus, a gram positive bacteria. The MIC values against P. aeruginosa for anydrofusarubin (1) and fusarubin methyl ether (2) were found to be 32- and 64-μg/ml respectively while the standard gentamycin showed MICs of 6.25 μg/ml (for S. aureus) and 12.5 μg/ml (for P. aeruginosa). The outcomes of our study suggest that anhydrofusarubin (1) and fusarubin methyl ether (2) are beneficial lead compounds to broaden the sphere of marketed antibacterial drugs.Bangladesh Pharmaceutical Journal 25(1): 80-88, 2022 (January)